Role of Triptans in the Management of Acute Migraine: A Review (Asian Journal of Pharmaceutics (AJP), 2016)
The common episodic headache disorder known as a migraine is mainly characterized by attacks comprising various combinations of a headache as well as neurological, gastrointestinal, and autonomic symptoms. This condition can be symptomatic of a distinct pathologic process or can occur without underlying causes. As per the report of American Migraine Prevalence and Prevention Study indicate that 17.1% of women and 5.6% of men in the United States experience one or more migraine headache per year. Most recurrent headaches are the result of a benign chronic primary headache disorder. The serotonin receptor agonists or triptans play a key role in migraine pharmacotherapy. The first and second generation of triptans is reported to give quick relief from migraine headache compare to other medication available. The importance of triptans is also reinstated by the fact that they are appropriate first line therapy for patients with mild to severe migraine and are used for rescue therapy when nonspecific medications are ineffective.